Percentage of Tumor Invasion at Pretreatment High-Resolution Magnetic Resonance Imaging: Associating With Aggressive and Tumor Response in Chinese T3 Rectal Cancer-Preliminary Results - Hu, Xiaoxin; Li, Jianwen; Sun, Yinan; Sun, Yiqun; Tong, Tong (Frontiers in Oncology, 2022)
Purpose: To assess the ability of percentage of tumor invasion (PTI) of T3 rectal cancer on MRI as an imaging biomarker to reflect aggressiveness and to predict tumor response after neoadjuvant chemoradiation. Methods: 107 rectal cancer patients who underwent MRI staging as T3 were included. The extramural depth of tumor invasion (EMD), the distance between outer border of muscularis propria (MP) and mesorectal fascia we called “thickness of the mesorectum (TM)”) at the same slice and direction were measured, and PTI was equal to EMD/TM, was calculated. The EMD and PTI of subgroups based on pretreatment CEA, CA19-9 levels; N stage and pathological complete response (pCR) were compared. The parameters, which described tumor invasion, were compared between pCR and non-pCR group. Student t-tests and logistic analysis were applied. Results: Before CRT, the PTI was shigher in CEA ≥ 5.2 ng/mL patients (58.52% ± 27.68%) than in CEA < 5.2 ng/mL patients (47.27% ± 24.15%) (p = 0.034). The EMD in non-pCR group (7.21 ± 2.85 mm) was higher than in pCR group (6.14 ± 3.56 mm) (p = 0.049). The PTI in non-pCR group was higher than in pCR group (p = 0.041). Compared with patients with PTI ≥ 50% and MRF (+), more patients with PTI < 50% and MRF (-) showed pCR (OR = 8.44, p = 0.005; OR = 6.32, p = 0.024). Conclusion: The PTI obtained on MRI may serve as an imaging biomarker to reflect tumor aggressiveness and predict which patients may benefit from CRT.